A review on e-learning development and implementation in developing countries (Case Study of Iran) - Omidinia, Siavash; Masrom, Maslin; Selamat, Harihuddin (2010)
E-Learning refers to the use of Information and Communications technology to enhance and/or support learning process. Today E-Learning in the context of education is a vital component.The objective of this paper is to review e-learning challenges in developing countries and specially to know what we have achieved in Iran, and what else we need to do make e-Learning as a major success which transforms Iran to knowledge society.Our finding have shown that the following factors can be attributed for hindering the success of e-Learning projects in Iran: process focus, implementation expertise, technology focus, open-source technology and one-time funding.